Late Immune-Related Adverse Events After At Least Two Years of Immune Checkpoint Inhibitor Therapy: Incidence and Association With Survival in Patients With Advanced NSCLC - Omar Elghawy, MD; Adam Barsouk, MD; Jonathan H. Sussman, BS; Benjamin A. Bleiberg, MD; Lauren Reed-Guy, MD; Christopher D’Avella, MD; Aditi Singh, MD; Christine Ciunci, MD, MSCE; Kyle Robinson, MD; John Kosteva, MD; Corey Langer, MD; Roger B. Cohen, MD; et al. (JTO Clinical and Research Reports)
Background: Limited data are available on late immune-related adverse events (IRAEs) in patients with metastatic NSCLC receiving immunotherapy (ICI) beyond 2 years. Methods: A single-institution retrospective analysis including patients who received longer than 2 years of ICI therapy for metastatic NSCLC between 2012 and 2023 was performed. Late IRAEs were defined as those occurring longer than 2 years after initiation of ICI therapy. The association of late IRAE with OS and PFS was assessed using an extended Cox regression with late IRAE modeled as a time-varying covariate. Results: In a cohort of 76 patients who received longer than 2 years of ICI, the median duration of treatment was 41.9 months, and 44 out of 76 (58%) experienced an early IRAE before 2 years. After 2 years on ICI, 38 out of 76 (50%) of patients experienced a late IRAE, many of whom (39%) had no previous early IRAE. Higher rates of late IRAEs were seen in females (p = 0.032), White patients (p = 0.041), and patients with previous grade 2 or higher IRAE (p = 0.020). Late IRAE occurrence was not associated with median progression-free survival or median overall survival. Conclusions: In patients receiving extended-duration ICI beyond 2 years, late IRAEs were common and often occurred in patients without previous history of IRAE. These findings support consideration of ICI discontinuation at 2 years.